Pemberdayaan UMKM melalui Sistem Pembayaran Digital, Kualitas Pelayanan, dan digital Marketing Pada Agen Beras Maju Jaya - Army Cahya Putra Rustamaji; Daspar Daspar; Erna Apriani; Arif Widodo Nugroho; Hafifah Aisya Putri Sabiya (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
Maju Jaya Rice Agent located in North Cikarang is an MSME engaged in the distribution and sale of rice and basic necessities. Despite having a strategic location and wide market potential, partners still face various operational obstacles, such as the dominance of cash transactions that limit consumer flexibility, the lack of a structured Standard Operating Procedure (SOP) for services, and the lack of optimal use of digital marketing. This Community Service (PKM) activity aims to increase the capacity and competitiveness of partners' businesses through the integration of digital payment systems, improving the quality of SOP-based services, and optimizing digital marketing strategies. The implementation method is carried out offline through five stages, namely socialization, service excellence training and inventory management, technology implementation, mentoring and evaluation, and preparation of SOP guidebooks for program sustainability. The results of the activity show that partners are now able to operate non-cash transactions through QRIS and e-wallets, manage spreadsheet-based bookkeeping, consistently implement service SOPs, and utilize digital media such as WhatsApp Business, Instagram, and Google Maps/Google Business Profile. This program has a positive impact on improving operational efficiency, governance professionalism, customer service quality, and expanding partner market reach in the digital era.